Using Text Sets to Facilitate Critical Thinking in Sixth Graders. Issue 2 (3rd April 2017) - Scales, Roya Q.; Tracy, Kelly N.
ABSTRACT: This case study examines features and processes of a sixth grade teacher (Jane) utilizing text sets as a tool for facilitating critical thinking. Jane's strong vision and student-centered beliefs informed her use of various texts to teach language arts as she worked to address demands of the Common Core State Standards. Text sets promoted multiple perspectives and fit with her beliefs about student empowerment. Despite contextual constraints, Jane used professional judgment to apply her learning from professional development to design and implement instruction. Findings support the idea that teachers need autonomy when choosing multiple texts across genres as well as effective strategies to engender critical thinking. Results can help guide further inquiry into types of teaching and classroom environments that facilitate or impede critical thinking.